THE PREVALENCE OF CRYPTOCOCCAL MENINGITIS IN HIV POSITIVE PATIENTS THAT ARE ON ANTIRETROVIRAL TREATMENT. A RETROSPECTIVE QUANTITATIVE STUDY PERFORMED AT DURBAN ADDINGTON HOSPITAL IN KZN, SOUTH AFRICA. - Zondi, Nobuhle; Shangase, Simangaliso (Student’s Journal of Health Research Africa, 2025)
Introduction HIV remains a global health challenge, with approximately 37.7 million people living with HIV in South Africa by 2020 (WHO). Among HIV-positive individuals, Cryptococcal meningitis (CM), a severe opportunistic infection, is a leading cause of morbidity and mortality. Despite the widespread use of antiretroviral therapy (ART), CM continues to be a major concern, especially in sub-Saharan Africa, where HIV prevalence is high. Aims and Objectives This study aimed to determine the prevalence of CM in HIV-positive patients on ART at Durban Addington Hospital between January and July 2022. The findings are intended to inform health practitioners on prevention strategies and treatment needs for this group. Methodology A retrospective quantitative approach was employed, analyzing medical and laboratory data from 137 HIV-positive patients. Cerebrospinal fluid (CSF) samples were tested for Cryptococcus neoformans, and the results were correlated with CD4 count and viral load data. This approach facilitated a statistical exploration of CM prevalence in HIV patients on ART. Results The study found that the majority of the participants were aged between 18 and 39 years. 17 patients (12.4%) tested positive for Cryptococcal antigen, indicating active CM infection. A significant portion of the cohort had low CD4 counts, putting them at higher risk for opportunistic infections. Additionally, 105 (76.6%) patients exhibited inadequate viral suppression, suggesting issues with ART adherence or treatment failure. Conclusion The study found a low prevalence of CM in HIV-positive patients on ART at Durban Addington Hospital. However, the high rate of advanced immunosuppression (low CD4 counts and high viral loads) highlights challenges in managing these patients and the need for improved diagnostic and monitoring practices. Recommendations Further longitudinal studies on adherence interventions, ART optimization, and integrated HIV care for opportunistic infections are recommended.